Risk of Sleepiness-Related Accidents in Switzerland: Results of an Online Sleep Apnea Risk Questionnaire and Awareness Campaigns - Lichtblau, Mona; Bratton, Daniel; Giroud, Philippe; Weiler, Thomas; Bloch, Konrad E.; Brack, Thomas (Frontiers in Medicine, 2017)
Abstract Objectives: Obstructive sleep apnea syndrome (OSAS) is associated with major morbidity and mortality but OSAS is frequently under recognized. To promote awareness of OSAS, the Swiss Lung League launched an online questionnaire combined with annual advertisements in mass media. Characteristics of participants, prevalence of sleep apnea, OSAS related symptoms, and their association with accidents were investigated. Methods: A questionnaire was created incorporating anthropometrics, the Epworth sleepiness scale (ESS), the OSAS domain of the sleep disorders questionnaire (SAS), and a question on accidents related to sleepiness. Results: 198,422 persons participated, 63% were male, mean (±SD) age was 45 (±16) y, weight 80 (±18) kg, height 173 (±9) cm and BMI 26.7 (±5.4) kg/m2. 19% male and 17% female participants had both elevated ESS and SAS scores (SAS>35 (m) /SAS>31 (f) and ESS>10) and were suspected of having sleep apnea (SA). 6654 (3.4%) had suffered an accident related to sleepiness. In multivariable regression analysis, ESS item #8 (falling asleep on the wheel, while stopping for a few minutes in traffic) was most strongly related to suffering an accident (OR 2.8). Conclusions: The OSAS awareness campaign of the Swiss Lung League reached a large number of people of both genders and of a wide age range. Many participants suffered from excessive sleepiness and symptoms of sleep apnea were highly prevalent. The campaign raised awareness of OSAS and contributed to the diagnosis and treatment of sleep apnea, thereby possibly preventing related morbidity and mortality.